Mixed worlds, segregated spaces: material culture, mestizaje and segmentation in the Aldeia site in Santarém (PA) - Symanski, Luís Claudio Pereira; Gomes, Denise Maria Cavalcante (Anais do Museu Paulista: História e Cultura Material, 2012)
This article discusses the processes of cultural exchange between Portuguese, Portuguese-Brazilian, Amerindians, and mestizos based on the analysis of the material culture from households of Santarém (PA), occupied during the eighteenth and nineteenth centuries,. Although these social groups manipulated material culture aiming to express different values, related to hierarchy, social segmentation, and affirmation of identities, ambiguity also characterizes these assemblages. This material ambiguity informs about the mixtures of both practices and cultural references that brought about the building of a mestizo society.